Thermodynamic characteristics of ternary sulfides MLn₂S₄ and solid solutions thereof - Kalinina, L.; Ushakova, Yu.; Medvedeva, O.; Shirokova, G.; Fominykh, E.; Ananchenko, B. (Functional Materials, 2006)
Thermodynamic characteristics of ternary sulfides MLn₂S₄ and soiid solutions thereof have been determined by EMF method in various modifications. The research results have shown that solid electrolytes CaGd₂S4 and BaTm₂S4 are stable compounds within the electrolytic range 653-723 K. The simultaneous determination of the binary sulfide activity in ternary BaTm₂S₄, CaY₂S₄, CaSm₂S₄, CaPr₂S₄ systems and of the cation and anion transfer numbers allowed us to estimate the phase stability limits and to propose a vacancy mechanism of defect formation and suggest the predominantly sulfide-ion type conductivity in the solid electrolytes studied. Методом ЭДС в различных модификациях определены термодинамические характеристики тернарных сульфидов MLn₂S₄ и твердых растворов на их основе. Проведенные исследования позволили считать твердые электролиты CaGd₂S4 и BaTm₂S4 устойчивыми соединениями в электролитическом интервале 653—728 К. Одновременное определение активности бинарных сульфидов в тернарных BaTm₂S₄, CaY₂S₄, CaSm₂S₄, CaPr₂S₄ и катионных и анионных чисел переноса сделало возможным оценить границы устойчивости фаз. предложить вакансионный механизм дефектообразования и преимущественно сульфид-ионный тип проводимости в исследуемых твердых электролитах. Методом ЕДС у різних модифікаціях виявлено термодинамічні характеристики тернарних сульфідів MLn₂S₄ і твердих розчинів на іх основі. Проведені дослідження дозволили вважати тверді електроліти CaGd₂S4 і BaTm₂S4 стійкими сполуками в електролітичному інтервалі 653-723 К. Одночасне виявлення активності бінарних сульфідів в тернарних BaTm₂S₄, CaY₂S₄, CaSm₂S₄, CaPr₂S₄, а також катіонних і аніонних чисел переносу зробило можливим оцінити межі стійкості фаз, запропонувати вакансійний механізм дефектоутворення і переважно сульфід-іонний тип провідності у твердих електролітах, що досліджувалися.